Ir(tri-N-Heterocyclic Carbene)-Catalyzed Production of Hydrogen and Cn Acids from Ethylene Glycol - Lee, Mi Hyun; Byeon, Heemin; Kim, Siwon; Yoon, Woojin; Park, Juneseo; Yun, Hoseop; Yu, Sungju; Jang, Hye Young (ACS Sustainable Chemistry and Engineering, 2023)
Novel tri-N-heterocyclic carbene (triNHC)-coordinated iridium catalysts (Ir(triNHC)) were employed for generating clean hydrogen and useful Cn acids from biomass-derived alcohols. The high efficiency and fast rate of hydrogen production (maximum turnover frequency = 13,080 h-1 and 485 L of H2/g-cat·h) from sustainable ethylene glycol were elucidated by the increased electron-richness of Ir(triNHC) complexes where three NHC ligands were coordinated to an iridium(I) ion. Elaborated mechanistic studies support the proposed reaction mechanisms forming H2 and Cn acids. This Ir(triNHC)-catalyzed process converting sustainable alcohols to useful fuels and chemicals is a promising carbon-neutral process.
Keywords: Carbenes; H 2 production; Higher efficiency; Hydroxy acids; Iridium catalyst; N-heterocyclic carbenes; Production of hydrogen; Sustainable; Tri-carbene; Α-hydroxy acid; ethylene glycol; H2 production; sustainable; tri-carbene; α-hydroxy acid